Statement on the work of the International Solidarity Fund for the Relief of Workers in Spain (circular) - Dalton, Hugh Dalton, Baron, 1887-1962 ; Citrine, Walter, 1887-1983 ; Middleton, J. S. ; Lindsay, H. Scott; Bevin, Ernest, 1881-1951
1937-01-20 018a-0022-001 292/946/18a/22(i)